A Computerized Tomography-Based Analysis of Spinal Canal Diameter to Study Its Implication on Cervical Spine Stenosis in Western Indian Population: A Retrospective Study - Purohit, Isha; Barath, Sitaram; Verma, Anjana; Modi, Kanishk; Purohit, Chelsi (Indian Journal of Neurosurgery, 2024)
Background The cervical spine is prone to various conditions necessitating early detection. Morphometric analysis through computed tomography (CT) scans plays a pivotal role in diagnosing and preventing severe diseases. This study focuses on understanding the morphometric details of the cervical canal in the West Indian population, addressing a geographical gap in existing literature. The primary objective of this study was to perform a morphometric analysis of the cervical spine to study the implications it can have on cervical canal stenosis in the West Indian population.Materials and Methods This study utilizes imaging data from the CT database of 100 individuals (73 men and 27 women). Measurements such as transverse canal diameter, sagittal canal diameter, cross-sectional canal surface area (CSA), and vertebral body diameter (VBD) were collected and the Pavlov-Torg ratio (PTR) was calculated from C2 to C7.Results Notable findings include significant differences in CSA and VBD between genders, while PTR indicated cervical damage in 40% of participants. Multinomial regression was applied which signified an association between weakness and PTR.Conclusion This study can be used to highlight the CT scan's importance in studying bony structures and the call for more region-specific morphometric studies. The variations in morphometric parameters could provide insights into understanding the vulnerabilities of a population belonging to a particular geographic area, in our case, the West Indian population.
Keywords: cervical stenosis; CT; functional imaging; spinal cord